The right speed and its value - Pacheco‐de‐Almeida, Gonçalo; Hawk, Ashton; Yeung, Bernard (Strategic Management Journal, 2015)
Slow investments cause substantial revenue losses, yet acceleration increases costs. This tradeoff implies that an optimal investment speed usually exists; it is faster the higher a firm's intrinsic speed capability. We hypothesize that it is a firm's intrinsic speed capability, rather than its speed relative to industry competitors per se, that boosts firm value. Using data on oil and gas facilities (1996–2005), we find that intrinsic speed capabilities augment firm value in a varied way: their value is larger with better corporate governance, lower cost of capital, and higher ability to draw value from R&D investment. Our work elevates the discussion of speed from a project‐level consideration to a firm‐level competitive advantage issue and raises the need to further explore its strategic value . Copyright © 2013 John Wiley & Sons, Ltd.